Community-Level Sanitation Coverage More Strongly Associated with Child Growth and Household Drinking Water Quality than Access to a Private Toilet in Rural Mali - Harris, Michael (2017)
Sanitation access can provide positive externalities; for example, safe disposal of feces by one household prevents disease transmission to households nearby. However, little empirical evidence exists to characterize the potential health benefits from sanitation externalities. This study investigated the effect of community sanitation coverage versus individual household sanitation access on child health and drinking water quality. Using a census of 121 villages in rural Mali, we analyzed the association of community latrine coverage (defined by a 200 m radius surrounding a household) and individual household latrine ownership with child growth and household stored water quality. Child height-for-age had a significant and positive linear relationship with community latrine coverage, while child weight-for-age and household water quality had nonlinear relationships that leveled off above 60% coverage (p < 0.01; generalized additive models). Child growth and water quality were not associated with individual household latrine ownership. The relationship between community latrine coverage and child height was strongest among households without a latrine; for these households, each 10% increase in latrine coverage was associated with a 0.031 (p-value = 0.040) increase in height-for-age z-score. In this study, the level of sanitation access of surrounding households was more important than private latrine access for protecting water quality and child health